Implementation of wireless sensor network in a smart home system - Qiu, Haojie (2014)
Description: Wireless Sensor Network for Smart Home system is for low-power and low-cost design target. Xbee module is used to build a complete Zigbee network and integrate with Arduino Leonardo board.